2022
DOI: 10.3389/fnagi.2022.785406
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hearing Loss and Hearing Aid Usage on the Visuospatial Abilities of Older Adults in a Cohort of Combined Hearing and Cognitive Impairment

Abstract: IntroductionIt has been proposed that hearing loss may result in improved visuospatial abilities. The evidence for this assertion is inconsistent, and limited to studies in congenitally deaf children, despite older adults with age-related hearing loss constituting the vast majority of the hearing impaired population. We assessed visuospatial (visuoconstruction and visuospatial memory) ability in older adult hearing aid users with and without clinically significant cognitive impairment. The primary aim of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Except for cognitive impairment, hearing loss might promote progress in certain cognitive function such as visuospatial abilities. Utoomprurkporn et al (Utoomprurkporn et al, 2022 ) found that patients with mild cognitive impairment and hearing loss performed as well as cognitively healthy subjects without hearing loss in tests of visuospatial abilities, thus reminding us to pay more attention to different aspects of cognitive functions instead of one certain domains when testing patients with cognitive impairment and hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…Except for cognitive impairment, hearing loss might promote progress in certain cognitive function such as visuospatial abilities. Utoomprurkporn et al (Utoomprurkporn et al, 2022 ) found that patients with mild cognitive impairment and hearing loss performed as well as cognitively healthy subjects without hearing loss in tests of visuospatial abilities, thus reminding us to pay more attention to different aspects of cognitive functions instead of one certain domains when testing patients with cognitive impairment and hearing loss.…”
Section: Discussionmentioning
confidence: 99%